2022
DOI: 10.3389/fonc.2022.859079
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Endoscopic Observations and Biopsy After Neoadjuvant Chemoradiotherapy in Assessing the Pathologic Complete Response of Patients With Esophageal Squamous Cell Carcinoma

Abstract: IntroductionNo standard method has been defined to evaluate the therapeutic response of esophageal cancer to neoadjuvant chemoradiotherapy (CRT). This study aimed to determine the predictive value of endoscopic evaluation and biopsy after CRT in predicting the complete pathological response to neoadjuvant CRT in patients with esophageal squamous cell carcinoma (SCC).Materials and MethodThis prospective, descriptive study was conducted on patients with stage II and III esophageal SCC who could undergo esophagec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…According to the criteria from 11th edition of the Esophageal Cancer Handling Regulations, endoscopic primary lesions were evaluated as follows: (1) all endoscopic findings suggestive of neoplastic lesions have disappeared, (2) there is pathologically no cancer detected by endoscopic biopsy of the primary lesion that was present before treatment, (3) the entire esophagus can be observed by endoscopy, (4) there are no endoscopic findings suggestive of active esophagitis (no swelling alteration, no white moss). A complete response was achieved when all of the above findings (1) to (4) were satisfied 16 . Patients who did not meet the response definition were categorized as non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…According to the criteria from 11th edition of the Esophageal Cancer Handling Regulations, endoscopic primary lesions were evaluated as follows: (1) all endoscopic findings suggestive of neoplastic lesions have disappeared, (2) there is pathologically no cancer detected by endoscopic biopsy of the primary lesion that was present before treatment, (3) the entire esophagus can be observed by endoscopy, (4) there are no endoscopic findings suggestive of active esophagitis (no swelling alteration, no white moss). A complete response was achieved when all of the above findings (1) to (4) were satisfied 16 . Patients who did not meet the response definition were categorized as non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…The CROSS trial, which was a benchmark for nCRT, showed a pCR rate of 49% in the squamous cell cancer group [5]. Similarly, another study done in Iran showed that 40.6% of the patients with SCC achieved pCR [15].…”
Section: Discussionmentioning
confidence: 95%
“…According to the criteria from 11th edition of the Esophageal Cancer Handling Regulations, endoscopic primary lesions were evaluated as follows: 1) all endoscopic ndings suggestive of neoplastic lesions have disappeared, 2) there is pathologically no cancer detected by endoscopic biopsy of the primary lesion that was present before treatment, 3) the entire esophagus can be observed by endoscopy, 4) there are no endoscopic ndings suggestive of active esophagitis (no swelling alteration, no white moss). A complete response was achieved when all of the above ndings 1) to 4) were satis ed 19 . Patients who did not meet the response de nition were categorized as non-responders.…”
Section: Treatment Evaluationmentioning
confidence: 99%